To simplify the expression (3g-4)-2(3g+4), you can start by applying the distributive property:
(3g-4)-2(3g+4) = 3g - 4 - 6g - 8
Next, you can combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, (3g-4)-2(3g+4) simplifies to -3g - 12.
(3g−4)−2(3g+4)
5 answers
wrong!
Apologies for the incorrect answer. Let's simplify the expression correctly.
(3g-4)-2(3g+4)
First, distribute the negative sign to both terms inside the parentheses:
= 3g - 4 - 2 * 3g - 2 * 4
Next, simplify the terms:
= 3g - 4 - 6g - 8
Now, combine like terms:
= 3g - 6g - 4 - 8
= (3g - 6g) - (4 + 8)
= -3g - 12
Therefore, (3g-4)-2(3g+4) simplifies to -3g - 12.
(3g-4)-2(3g+4)
First, distribute the negative sign to both terms inside the parentheses:
= 3g - 4 - 2 * 3g - 2 * 4
Next, simplify the terms:
= 3g - 4 - 6g - 8
Now, combine like terms:
= 3g - 6g - 4 - 8
= (3g - 6g) - (4 + 8)
= -3g - 12
Therefore, (3g-4)-2(3g+4) simplifies to -3g - 12.
no that's not the answer
I apologize for the confusion. Let's simplify the expression correctly.
(3g-4)-2(3g+4)
First, distribute the -2 to both terms inside the parentheses:
= 3g - 4 - 2 * 3g - 2 * 4
= 3g - 4 - 6g - 8
Next, combine like terms:
= (3g - 6g) - (4 + 8)
= -3g - 12
Therefore, (3g-4)-2(3g+4) simplifies to -3g - 12.
(3g-4)-2(3g+4)
First, distribute the -2 to both terms inside the parentheses:
= 3g - 4 - 2 * 3g - 2 * 4
= 3g - 4 - 6g - 8
Next, combine like terms:
= (3g - 6g) - (4 + 8)
= -3g - 12
Therefore, (3g-4)-2(3g+4) simplifies to -3g - 12.